A Morphosyntactical Analysis of University Students’ Writing: Indonesian Case (e-Journal of Linguistics, 2020)
Different grammar between languages often causes confusionto those who learn it. Students often experience suchproblems when their first language (L1) and the targetlanguage (L2) share very limited linguistic aspects. Thisstudy aims to focus on the morphosyntactic issues that lead tothe grammatical errors which take place in the Englishwriting of Indonesian university students taking writing classand to analyze the potential sources of their mistakes. Thedata from this study were collected from a writingassignment in three Writing classes. This research followedthe steps initiated by James (1998), among others: collectingdata, identifying errors, classifying errors, explaining errors,and finding sources of errors. The results revealed that of the2.218 grammatical errors found, they could be classified intotwo main error types: morphological errors (81.97%) andsyntactic errors (18.03%) which were divided into 32 specificerrors. The findings suggest that the Indonesian students arenot fully aware how to use the plural marker ‘s’ as well the‘3rd singular’ in present tense. Moreover, they cannot build asimple sentence due to the different word-order and sentencestructure between Indonesian and English in terms ofmorphology and syntax.With regard to the potential sourcesof error, both inter-language errors and intralingual errors anddevelopments have an influence on errors made in writing.Errors between languages occur when students try to usetheir knowledge of the L1 structure to obtain the targetlanguage, but the differences between the two languagescause errors. Intralingual and developmental errors are foundbecause of difficulties and problems in the target languageitself. The findings in this study are very useful for theprocess of learning English especially in writing skills.
Keywords: Morphological errors; Syntactic errors; Intralingual and developmental errors